EFL in a Multilingual Nation: Balancing Bahasa Indonesia and English in the Elementary Classroom - Coloquit, Lorie Mae; Makmuroh, Umniyyatul (Universitas PGRI Semarang, 2025)
Indonesia’s multilingual landscape poses both opportunities and challenges for English language learning in primary education, where Bahasa Indonesia serves as the main instructional language alongside the introduction of English. Grounded in Vygotsky’s Sociocultural Theory and Translanguaging Theory, this study explored how fifth-grade students and their teacher at SD Hj. Isriati Baiturahman 1 Semarang navigate the interplay between Bahasa Indonesia and English in the classroom. Using a qualitative case study design, data were collected through classroom observations, interviews, and document analysis. Findings revealed that students used Bahasa Indonesia as a cognitive and emotional scaffold to support English comprehension, while English was employed primarily for structured classroom tasks and oral practice. Translanguaging emerged as a natural learning strategy that facilitated meaning-making, confidence, and participation. Students demonstrated positive attitudes toward bilingual instruction, perceiving it as both supportive and empowering. The study concludes that balanced bilingual practices enhance engagement, promote additive bilingualism, and nurture linguistic identity among young learners. The implication highlights the need for EFL teachers and policymakers in Indonesia to embrace multilingual pedagogy that integrates Bahasa Indonesia strategically to foster inclusive, meaningful, and culturally responsive English learning.